Serum IGF-I and IGFBP-3 levels of Turkish children during childhood and adolescence: Establishment of reference ranges with emphasis on puberty - BEREKET, ABDULLAH; ÖZEN, AHMET OĞUZHAN; DEMİRCİOĞLU, SERAP (KARGER, 2006)
3Aims/Methods: We established age- and sex-related reference ranges for serum insulin-like growth factor-I (IGF-I) and insulin-like growth factor binding protein-3 (IGFBP-3) levels in 807 healthy Turkish children (428 boys, 379 girls), and constructed a model for calculation of standard deviation scores of IGF-I and IGFBP-3 according to age, sex and pubertal stage. Results: Serum IGF-I and IGFBP-3 concentrations tended to be higher in girls compared to boys of the same ages, but the differences were statistically significant only in pubertal ages (9-14 years) for IGF-I and only in prepubertal ages for IGFBP-3 (6-8 years) (p < 0.05). Peak IGF-I concentrations were observed earlier in girls than boys (14 vs. 15 years, Tanner stage IV vs. V) starting to decline thereafter. IGFBP-3 levels peaked at age 13 and at Tanner stage IV in both sexes with a subsequent fall. Serum levels of IGF-I and IGFBP-3 increased steadily with age in the prepubertal stage followed by a rapid increase in IGF-I in the early pubertal stages. A relatively steeper increase in IGF-I but not in IGFBP-3 levels was observed at age 10-11 years in girls and at 12-13 years in boys which preceded the reported age of pubertal growth spurt. At late pubertal stages, both IGF-I and IGFBP-3 either did not change or decreased by increasing age. Interrelationships between growth factors and anthropometric measurements have been described, and the physiologic consequences of these have been discussed in detail. Conclusions: Differences in the pattern of IGF-I and IGFBP-3 in the present paper and those reported in other studies emphasize the importance of locally established reference ranges. Establishment of this reference data and a standard deviation score prediction model based on age, sex and puberty will enhance the diagnostic power and utility of IGF-I and IGFBP-3 in evaluating growth disorders in our population. Copyright (c) 2006 S. Karger AG, Basel.
Keywords: insulin-like growth factor-I; insulin-like growth factor binding protein-3; puberty,IGF-I and IGFBP-3 levels; healthy children,IGF-I and IGFBP-3 levels; IGF-I and IGFBP-3,reference ranges; GROWTH-FACTOR-I; BINDING PROTEIN-3 IGFBP-3; BODY-MASS INDEX; HORMONE DEFICIENCY; REFERENCE VALUES; INSULIN; AGE; SEX; PLASMA; DISORDERS